Development of an organic coating powder and optimization of process parameters for shelf life enhancement of button mushrooms (Agaricus bisporus). Issue 3 (2nd February 2021) - Thakur, Rajeev Ranjan; Shahi, Navin Chandra; Mangaraj, Shukadev; Lohani, Umesh Chandra; Chand, Khan
Abstract: Button mushrooms ( Agaricus bisporus ) were coated by dissolving four different organic coating material viz. apple peel powder (1.0 to 1.4% wt/vol), carboxymethyl cellulose (1.2 to 1.8% wt/vol), tartaric acid (0.375%), and glycerol monostearate (1%) in distilled water and dipping the mushroom in coating solution for 45 to 75 s. Experiments were conducted using response surface methodology and the coated as well as uncoated samples were stored at ambient and refrigerated conditions. Various quality parameters of button mushroom were measured. Results indicated that the mushroom coated at optimum condition (apple peel powder 1.17% wt/vol, carboxymethyl cellulose 1.8%, and dipping time 75 s) maintained high level of quality parameters and were used to develop the organic coating powder. The use of coating powder for coating under ambient and refrigerated condition has the potential to maintain mushroom quality and prolong its postharvest shelf life up to 5 and 9 days, respectively. Practical applications: The efficacy of developed organic coating powder tested on button mushroom (Agaricus bisporus) shows some prominent practical application for fresh produce. From the analysis and interpretation of the experimental results it was found that the developed organic coating powder was effectively increased the shelf life of button mushroom and also maintained its quality characteristics during storage, and hence, can be a promising as an edible coating for practical use as well as in commercial postharvest applications to enhance the storage life of button mushroom and other fresh produce.